Understanding Metal Induced Recombination Losses in Silicon Solar Cells with Screen Printed Silver Contacts. (November 2016) - Inns, Daniel
Abstract: There have been great improvements in silicon solar cell voltage across the last 5 years. A great deal of the gains can be attributed to application of lighter phosphorus emitter diffusions which deliver higher cell voltages, combined with the complementary silver metallization pastes which can contact those emitters. As the voltages continue to increase over time, metal recombination losses become more important to understand. The surface doping, junction depth, and metal contact used are all factors in determining the metal recombination rate which covers a range of approximately 400-1500 fA/cm 2 for standard cases. Silver contact pastes modulate recombination by changing the way they etch the emitter surface, and semiconductor models indicate that the recombination rate can decrease to < 200 fA/cm 2 as metallization paste technology continues to improve.